JavaScript moving to ES2015 : explore and master modern JavaScript techniques with ES2015 in order to build large-scale web applications - Antani, Ved; Timms, Simon; Prusty, Narayan (Packt Publishing, 2016)
Explore and master modern JavaScript techniques with ES2015 in order to build large-scale web applications About This Book This course offers an expert's eye on the latest ES6 features and how these advanced tasks fit together in JavaScript as a whole Discover robust JavaScript implementations of classic and advanced design patterns Learn about modern web architectures and build real-world apps on top of them Who This Book Is For This course is for experienced developers familiar with other object-oriented languages who wants to learn new capabilities of ES-2015 to improve their web development skills and build professional-quality web applications. This also goes for those who want to explore some modern JavaScript features, techniques, and architectures in order to develop cutting-edge web applications. What You Will Learn Get a run through of the basic language constructs, Functions, and Closures of JavaScript Code using the powerful object-oriented feature in JavaScript Master DOM manipulation, cross-browser strategies, and ES6 Harness the power of patterns for tasks ranging from application building to code testing Identify the best use cases for microservices Gain expertise in responsive and dynamic website design Enable real-time communications between client-client and client-server/server-client Write complete applications using functional reactive programming In Detail JavaScript is a high-level, dynamic, untyped, lightweight, and interpreted programming language. Mastering modern JavaScript techniques and the toolchain are essential to develop web-scale applications. This Learning Path will upgrade your skills to ES2015, and you will get to introduce yourself to popular frameworks like React and Angular 2. In the first module, you will get familiar with the language constructs and how to make code easy to organize. You will gain a concrete understanding of variable scoping, loops, and best practices on using types and data structures, as well as the coding style and recommended code organization patterns in JavaScript. By the end of the module, you will understand how reactive JavaScript is going to be the new paradigm. Over the course of the next module, you will explore how design patterns can help you improve and organize your JavaScript code. You'll get to grips with creational, structural, and behavioral patterns and get a deeper look at patterns used in functional programming, as well as model view patterns and patterns to bui...
"Learning path.". - Includes bibliographical references and index. - Description based on online resource; title from cover (viewed April 18, 2017)
Keywords: JavaScript (Computer program language); Functional programming (Computer science); JavaScript (Langage de programmation); Programmation fonctionnelle